Wacana Kritis pada Pemberitaan Makanan Bergizi Gratis (MBG) dalam Media Massa - Zulmi Zul Zakiyah; Desma Yuliadi Saputra; Rina Andriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Media coverage of the Free Nutritious Meals (MBG) program not only serves to convey information but also plays a role in shaping public perceptions of government policies. This study aims to analyze the critical discourse in news coverage of the Free Nutritious Meals (MBG) program in the mass media using Teun A. van Dijk’s Critical Discourse Analysis model. The research method employed is qualitative, utilizing documentation and content analysis techniques on three news texts from the online media outlets Kompas.com, Tempo.com, and CNN Indonesia. The analysis focused on macro, superstructure, and micro structures, encompassing semantic, syntactic, stylistic, and rhetorical aspects. The results indicate that all three media outlets tend to portray the government as the dominant and responsible actor in implementing the MBG program, while issues or criticisms regarding the program are presented sparingly and often softened through specific language choices. These findings indicate the presence of power relations and ideology at work in the construction of MBG news discourse. This study is expected to enhance readers’ critical awareness of media texts and encourage more balanced and objective journalistic practices.